THE ROLE AND IMPORTANCE OF PEDAGOGICAL EDUCATION IN THE TRAINING OF HIGHLY QUALIFIED PERSONNEL (Universal International Scientific Journal, 2026)
The article discusses the essence of pedagogical erudition and its importance in training highly qualified pedagogical personnel. In the modern education system, it is important for a teacher to have a broad outlook, deep knowledge and professional competencies. The article scientifically analyzes the role of pedagogical erudition in the work of a teacher, its role in increasing the effectiveness of the educational process, and the issues of forming these qualities in future teachers.
Keywords: pedagogical erudition, pedagogical competence, quality of education, qualified personnel, pedagogical skills, professional development, modern education.